1997
DOI: 10.1111/j.1439-0396.1997.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Soya and casein as dietary proteins for dogs

Abstract: Summary In a study with four adult dogs isolated soya protein and casein were compared as protein sources in canine diets with regards to digestibility, plasma concentrations of amino acids and some biochemical variables in the plasma. Casein and soya protein were highly digestible (apparent digestibility of crude protein: 85–90%). The plasma aminograms were influenced by dietary proteins and also subjected to postprandial changes (blood samples obtained in fasted dogs or 6 h postprandially). With soya protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Staple foods are important determinants of health in humans and companion animals (Public Health Service, 1988;Hand, 2000). Developing nutritional guidelines to improve health and prevent disease in dogs has contributed to the production of numerous commercial dog foods with novel carbohydrate (Fortes et al, 2010), fi ber (Bednar et al, 2001;Swanson et al, 2001), and protein sources (Zentek and Mischke, 1997;Dust et al, 2005). Despite the success of plant-based nutrients in dog food, dry bean (Phaseolus vulgaris L., Fabaceae) is one staple food crop of global agricultural and nutritional importance that has been overlooked in commercial pet food formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Staple foods are important determinants of health in humans and companion animals (Public Health Service, 1988;Hand, 2000). Developing nutritional guidelines to improve health and prevent disease in dogs has contributed to the production of numerous commercial dog foods with novel carbohydrate (Fortes et al, 2010), fi ber (Bednar et al, 2001;Swanson et al, 2001), and protein sources (Zentek and Mischke, 1997;Dust et al, 2005). Despite the success of plant-based nutrients in dog food, dry bean (Phaseolus vulgaris L., Fabaceae) is one staple food crop of global agricultural and nutritional importance that has been overlooked in commercial pet food formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs fed PLANT showed no differences in indicators of energy metabolism or protein synthesis (118) , with serum glucose and protein levels, BW and LST all maintained and comparable to the MEAT-fed dogs. Furthermore, previous studies have demonstrated comparable digestibility of plant-based proteins in dogs fed plant-or chickenbased iso-nitrogenous diets (119)(120)(121)(122) . Soya, a plant-based protein, has been reported to be beneficial for dogs with hepatic disease, as the amino acid profile may positively influence protein and amino acid metabolism and decrease blood ammonia levels (122) .…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, previous studies have demonstrated comparable digestibility of plant-based proteins in dogs fed plant-or chickenbased iso-nitrogenous diets (119)(120)(121)(122) . Soya, a plant-based protein, has been reported to be beneficial for dogs with hepatic disease, as the amino acid profile may positively influence protein and amino acid metabolism and decrease blood ammonia levels (122) . It is thus unclear if the protein quantity or quality in PLANT contributed to the lower BUN in the dogs fed PLANT.…”
Section: Discussionmentioning
confidence: 88%
“…8a uf die »Besonderheit des Inhaltsv on Produkten und Dienstleistungen«. 800 Es bedürfeauch im Urheberrechteiner »aktiven Rezeption, Interpretation und Beeinflussung der europäischen Vo rgaben im Lichte der jeweiligen nationalen Tradition«. 801 Im Ergebnis enthielten daher weder die urheberrechtlichen Richtlinien noch die Rechtsprechung des Europäischen Gerichtshofs eine klare Aussage füroder gegen einen einheitlichen We rkbegriff.…”
unclassified